Overexpression of human RAD51 and RAD52 reduces double-strand break-induced homologous recombination in mammalian cells - Kim, Perry M. (Oxford University Press, 2001)
Double-strand breaks (DSBs) can be repaired by homologous recombination (HR) in mammalian cells, often resulting in gene conversion. RAD51 functions with RAD52 and other proteins to effect strand exchange during HR, forming heteroduplex DNA (hDNA) that is resolved by mismatch repair to yield a gene conversion tract. In mammalian cells RAD51 and RAD52 overexpression increase the frequency of spontaneous HR, and one study indicated that overexpression of mouse RAD51 enhances DSB-induced HR in Chinese hamster ovary (CHO) cells. We tested the effects of transient and stable overexpression of human RAD51 and/or human RAD52 on DSB-induced HR in CHO cells and in human cells. DSBs were targeted to chromosomal recombination substrates with I-SceI nuclease. In all cases, excess RAD51 and/or RAD52 reduced DSB-induced HR, contrasting with prior studies. These distinct results may reflect differences in recombination substrate structures or different levels of overexpression. Excess RAD51/RAD52 did not increase conversion tract lengths, nor were product spectra otherwise altered, indicating that excess HR proteins can have dominant negative effects on HR initiation, but do not affect later steps such as hDNA formation, mismatch repair or the resolution of intermediates.